Analisis Faktor – Faktor yang Mempengaruhi Tarikan Perjalanan Menuju Mall Transmart Carrefour - Nurwanda Sari (UNIVERSITAS LAMPUNG, 2019)
The movement of the flow of people, vehicles and goods results in a variety of interactions. Almost all interactions require travel and produce traffic flow movements. One of them is the shopping movement that has several alternative destinations including traditional markets, supermarkets, department stores, plazas, malls and so on. Currently department stores are the right alternative - for consumers because there are various human needs available. In Lampung Transmart Carrefour Mall provides a parking area on one basement floor with a car park capacity of approximately 150 vehicles and added parking capacity in the area around the mall for cars and motorbikes that cannot fully accommodate the vehicles of visitors who come to visit due to the attraction of the mall facilities. Data retrieval is done by means of questionnaire surveys on weekdays and weekends, namely surveys of visitor attraction coming from Lampung Transmart Carrefour Mall. The data processing method used the Statistical Package for the Social Sciences (PSPP) Program, and analysis using multiple regression analysis. Visitors who come on weekday with an average of 10,140 people, and on weekends the most 26,367 people per day. In this travel attraction, the fac - tors that influence are the Visitor Origin Factor (X1), the Vehicle Parking Location Factor (X4), and the Factors of Visiting the Mall (X5). These three factors have a correlation value of